Beyond yellow: discovery and genetic dissection of an apricot petal color in Brassica juncea L - Li, Ri hui; Zhang, Xiao xue; Yuan, Kai wen; Zhao, Yan li; Quan, Cheng tao; Wang, Kai xuan; Guan, Rong zhan; Lu, He jun; Miao, Jia shun; Zhang, Dong qing (Frontiers in Plant Science, 2026)
Brassica juncea is an important oilseed and vegetable crop whose flowers are typically yellow, largely owing to carotenoid pigmentation. Here, we report a novel, heritable apricot-flowered variant designated ‘Caijie,’ from a wild B. juncea accession. Metabolomic profiling revealed that the distinctive petal coloration was primarily attributable to anthocyanin accumulation. Genetic mapping via bulked segregant analysis (BSA) mapped the apricot-flowered trait to a single dominant locus within a 9.76-Mb interval on chromosome B03. Among the 1,406 annotated genes in this region, Production of Anthocyanin Pigment 2 (BjB03.PAP2), which encodes an R2R3-MYB transcription factor, emerged as the most likely candidate gene. Consistent with this, transcriptomic analysis revealed coordinated upregulation of multiple structural genes involved in the anthocyanin biosynthesis pathway in the apricot-flowered variant. Further sequence analysis revealed a (TC)n dinucleotide repeat polymorphism in the promoter of BjB03.PAP2, representing a structural variation that is likely responsible for enhanced transcriptional activity and subsequent anthocyanin production in petals. This study unveils a previously unrecognized genetic mechanism underlying flower color variation in B. juncea, offering new insights into the evolution of floral pigmentation and a valuable genetic resource for breeding ornamental Brassica crops.